Evaluation of Metformin Plus Insulin Versus Insulin-Only in Preventing Pre-Eclampsia in Pregnant Women with Gestational Diabetes Mellitus: A Randomized Single-Blind Clinical Trial - Javaheri Koupaei, Sedigheh; Farahbod, Farinaz; Movahedi, Minoo; Zarean, Elahe; Khanjani, Somayeh; Danesh Shahraki, Azar; Najarnejad, Amirmehdi (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: Gestational Diabetes Mellitus (GDM) is associated with an increased risk of pregnancy complications. The present study aimed to evaluate the effect of combined metformin and insulin therapy compared to insulin alone in preventing pre-eclampsia among pregnant women with GDM. Methods: This randomized interventional clinical trial was conducted on 150 women with GDM in Isfahan from 2021 to 2023. Women in the insulin-only group received intermediate-acting insulin such as Neutral Protamine Hagedorn (NPH), at a dose of 0.2 units/kg. In the group treated with metformin p l u s insulin, a similar method was used, starting with an initial dose of 500 mg of metformin twice daily. The results were analyzed using SPSS software version 19. Results: The number of patients with protein excretion in the insulin group was significantly higher than that in the insulin-plus-metformin group (P=0.006). Additionally, the insulin dose used in the insulin-plus-metformin group was significantly lower than in the insulin-only group (P=0.013). A significant difference was observed in the gestational age at study entry in patients with other pregnancy complications (P=0.04). Conclusion: Adding metformin to insulin therapy in pregnant women with GDM may help reduce insulin requirements and the incidence of proteinuria in those who develop pre-eclampsia, without increasing other pregnancy complications.